Hubungan antara Self-Concept dan Toxic Disinhibition Online Effect pada Mahasiswa yang Menggunakan Media Sosial Instagram - Ruli Gustian Nugraha; Kristin Rahmani; Efnie Indrianie; Dinta Nurannisa Aliifah (Universitas Kristen Maranatha, 2022)
This study aims to determine relationship between self-concept and toxic disinhibition online effect on students who use social media Instagram. The measuring instrument used is the Toxic Disinhibition Online Effect Scale and the Self-concept scale. The population in this study were students using Instagram. The research methods is a quantitative method. This research was conducted for twelve months, where it was found that out of 170 students, more than half (51,23%) had a positive self-concept. Based on the results of statistical tests the significance values is 0.200. The significance value in this study is greater than 0.05 with a correlation value of -0.065. Based on this, it can be concluded that there is no relationship between self-control and toxic disinhibition online effect, so it is recommended that students who have a positive self-concept should maintain the frequency, duration, and intensity of social media use as a form of prevention so that there is no toxic disinhibition online effect.